Seni Dan Kebudayaan Dalam Pendekatan Hermenutik / Interpretif - Guntur Guntur (Ornamen, 2007)
This writing tries to look for the most appropriate definition of art to examine the art phenomenon with hermeneutics/ interpretive perspective. Some definitions considered include art as mimetic, art as language and art as presentational symbol. In order to get conformity with the approach used in a research, discussion concerning definition of culture, particularly cultural theory emphasizing on the symbol system, is also included in this study. In the last section, the conclusion is conveyed by balancing between definition of art and definition of culture considered as appropriate to use as the footing in hermeneutics/ interpretive perspective-based study. Keywords: Art, Hermeneutic, Interpretive.